PENGARUH GAJI DAN LINGKUNGAN KERJA TERHADAP PROFESIONALISME (Pada Pegawai BPKP Provinsi Bengkulu) - Hengki Setiawan; Eka Sri Wahyuni; Yenti Sumarni (Bajang Institute, 2025)
This study aims to determine the effect of salary and work environment on employee professionalism at the Financial and Development Supervisory Agency (BPKP) of Bengkulu Province. The method used is associative quantitative with a census approach to the entire employee population of 81 people. Data were collected through a questionnaire with a Likert scale and analyzed using multiple linear regression. The results of the study indicate that both salary and work environment have a significant effect on employee professionalism. Validity and reliability tests prove that the instruments used are valid and reliable. The results of the classical assumption test indicate that the regression model does not contain problems of normality, multicollinearity, or heteroscedasticity. Partially, the salary variable has a positive effect of 0.469 on professionalism, while the work environment has a greater effect of 0.530. Both variables together contribute to increasing employee professionalism. This finding emphasizes the importance of a balance between compensation and work environment quality in supporting the professional performance of government employees